Broadcasting the Italian voice's broadcasting: opera and Italy on the air, 1920s–1930s. Issue 4 (8th August 2022) - Vella, Francesca
ABSTRACT: Within the early twentieth-century Italian radiophonic imagination, opera occupied a complex position. The overriding 'voice' of Italy and its radio empire under Fascism, opera supported the new technology as a political and cultural tool, even as it challenged it as a geographical and perceptual fantasy. This article has two aims. First, drawing on materials from 1920s and '30s radio magazines, it sketches a history of early radio listening that restores vision and touch to a more central position than they have had in previous scholarly accounts. Second, it investigates radio and the Italian operatic voice as two mutually broadcasting technologies, ones whose critical co-construction was more than an accident of the fraught political moment. Contemporary definitions of radio as bel canto and of bel canto as radiophonic rested on a subtler, conceptual alignment between the two media, each of which foregrounded a tension between sound and meaning and implied the radial dissemination of voice 'out' in all directions. This article thus seeks to answer two questions. Did opera, a fundamentally audiovisual genre, become invariably 'sonified' through radiophonic transmission? And what happened when that old broadcasting technology, the Italian voice, met the new communications medium?